Why do listed companies in China have incentive preference of the equity finance? - Wang, dongxiao (2009)
The choice of company capital structure can do great influence to the efficiency of the value and allocation of resources. In general, the finance methods comprise of internal finance and external finance, based on whether the funds come from the inside or outside of the corporation.